Evidence for a Supraspinal Contribution to the Human Crossed Reflex Response During Human Walking - Mrachacz-Kersting, Natalie; Gervasio, Sabata; Marchand-Pauvert, Veronique (Frontiers in Human Neuroscience, 2018)
IIn humans, an ipsilateral tibial nerve (iTN) stimulation elicits short-latency-crossed-responses (SLCR) comprised of two bursts in the contralateral gastrocnemius lateralis (cGL) muscle. The average onset latency has been reported to be 57-69 ms with a duration of 30.4±6.6 ms. The aim of this study was to elucidate if a transcortical pathway contributes to the SLCR. In experiment 1 (n=9), single pulse supra-threshold transcranial magnetic stimulation (supraTMS) was applied alone or in combination with iTN stimulation (85% of the maximum M-wave) while participants walked on a treadmill (delay between the SLCR and the motor evoked potentials (MEP) varied between -30-200 ms). In experiment 2 (n=6), single pulse sub-threshold TMS (subTMS) was performed and the interstimulus interval varied between 0-30 ms. In experiment 3, somatosensory evoked potentials (SEPs) were recorded during the iTN stimulation to quantify the latency of the resulting afferent volley at the cortical level. SLCRs and MEPs in cGL occurred at 63±6 ms and 29±2 ms, respectively. The mean SEP latency was 30±3 ms. Thus, a transcortical pathway could contribute no earlier than 62-69 ms (SEP+MEP+central-processing-delay) after iTN stimulation. Combined iTN stimulation and supraTMS resulted in a significant MEP extra-facilitation when supraTMS was timed so that the MEP would coincide with the late component of the SLCR, while subTMS significantly depressed this component. This is the first study that demonstrates the existence of a strong cortical control on spinal pathways mediating the SLCR. This likely serves to enhance flexibility, ensuring that the appropriate output is produced in accord with the functional demand.